Patient-reported complications related to colonoscopy: a prospective feasibility study of an email-based survey. (1st April 2019) - Steffenssen, Mia W.; Al-Najami, Issam; Zimmermann-Nielsen, Erik; Baatrup, Gunnar
Abstract: Objective: This prospective pilot study assessed the feasibility of electronic email-based questionnaires about patient-reported complications after colonoscopy. Material and methods: A newly internally validated questionnaire on patient-reported complications related to colonoscopy was conducted as an online survey. Results: Out of 200 patients (mean age 65 years), 83% completed the first questionnaire immediately after the procedure, 77% completed the second follow-up questionnaire after 24 h at home, and 70% the third one after 30 d. Forty-four percent of the patients reported minor adverse events after 24 h, and 23% at the follow-up after 30 d. The rate of sick leave in the 30-d period after the colonoscopy was 6%. Conclusions: This study shows that email-based questionnaires give a high response rate independent of age or gender, but that the response rate declines with time after colonoscopy. Minor adverse events are underestimated, and colonoscopy could lead to sick leave in a minor subgroup of patients.